2010
DOI: 10.5897/ajb10.1819
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid (ABA)-mediated inhibition of seed germination involves a positive feedback regulation of ABA biosynthesis in Arachis hypogaea L.

Abstract: Abscisic acid (ABA) plays an important role in seed dormancy, embryo development and adaptation to environmental stresses. We found that imbibition of exogenous ABA by peanut seeds led to a significant increase in the levels of both AhNCED1 gene [a key gene encoding nine-cis-epoxycarotenoid dioxygenase (NCED) involved in ABA biosynthesis in peanut] transcript and endogenous ABA in germinating seeds, and also led to a marked decrease in α-amylase activity, germination rate and viability index of germinating see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 42 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Only lowering the auxin concentration (that is, removing the ‘on’ switch) does not reduce other phytohormones. Considering this hypothesis, a second ‘on’ switch may be required to accurately determine the time frame for cell enlargement [ 25 30 ]. It was found that the content of ABA is different in embryogenic cell clusters, globular embryos, torpedo embryos, and cotyledon embryos [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only lowering the auxin concentration (that is, removing the ‘on’ switch) does not reduce other phytohormones. Considering this hypothesis, a second ‘on’ switch may be required to accurately determine the time frame for cell enlargement [ 25 30 ]. It was found that the content of ABA is different in embryogenic cell clusters, globular embryos, torpedo embryos, and cotyledon embryos [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of LeNCED1 in Lycopersicon esculentum delays seed germination (Thompson, et al 2000). AhNCED2 plays a positive role in maintaining seed dormancy in Arachis hypogaea (Bo, et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Short and shallow dormancy may result in the harmful phenomenon-of pre-harvest sprouting, in which the seeds gain the ability to germinate while they are still on the mother plant (Kermode, 2004). The process triggers in the final stage of maturation of the seed, at the end of the cell cycle and is controlled by several genes and environmental factors, with broad hormonal influence (Hu et al, 2010;Footitt et al, 2014).…”
Section: Introductionmentioning
confidence: 99%